Perceptions of Fitness Enthusiasts on the Role of Music in Enhancing Exercise Motivation - Kevin Surya Pratama; Rizal Ahmad Fauzi; Adang Sudrazat (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This study aimed to examine fitness enthusiasts’ perceptions regarding the role of music in enhancing exercise motivation during gym-based physical activity. The study employed a quantitative descriptive design using a survey method. Data were collected through a closed-ended questionnaire with a five-point Likert scale distributed to 50 fitness enthusiasts who routinely exercised in several fitness centers in Cirebon. The questionnaire measured participants’ perceptions regarding the influence of music on exercise motivation, focus, enjoyment, workout intensity, and exercise consistency. Data were analyzed using descriptive statistics, including frequencies, percentages, and mean scores. The findings showed that all questionnaire items obtained mean scores ranging from 3.92 to 4.34, indicating high to very high perception categories. The highest mean score was found in the statement that music makes exercise sessions more enjoyable (M = 4.34), followed by the statement that participants enjoy workouts more while listening to music (M = 4.26). Overall, respondents positively perceived music as an important factor supporting exercise motivation, concentration, enjoyment, workout consistency, and perceived exercise performance. These findings suggest that music may serve as an effective psychological support strategy in fitness activities.